Allergic Asthma-Induced Cognitive Impairment is Alleviated by Dexamethasone - Ren, Mengli; Feng, Min; Long, Zhimin; Ma, Jing; Peng, Xuehua; He, Guiqiong (Frontiers in Pharmacology, 2021)
Allergic asthma is a typical chronic inflammatory disease of respiratory tract. Clinical data shows that patients with allergic asthma have different degrees of cognitive dysfunction. The molecular mechanism underlying the pathogenesis of asthma-induced cognitive disorder is not yet well defined. Dexamethasone (DEX), one of the first-line drugs being widely used in the treatment of asthma, has not been reported to have an effect on cognitive dysfunction in mice model. To investigate the effect of asthma on cognitive impairment as well as the effect of DEX on asthma-caused morphological and behavioral changes, C57BL/6J mice received treatment with house dust mites (HDM) for 60 days to become allergic asthma model mice, and a group of HDM-treated asthma model mice were treated with DEX. HDM-treated asthma model mice exhibited increased airway hyperresponsiveness (AHR) and inflammatory infiltration in lung tissue. An elevated level of IL-4, IL-5, and TNF-α was detected in bronchoalveolar lavage fluid (BALF) by Luminex liquid suspension chip. Asthma model mice also presented memory deficits accompanied with morphological changes at the synaptic levels in the cortex and hippocampus. Meanwhile, vascular edema and increased expression of HIF-1α and HIF-2α were found in the brain of asthma model mice. Interestingly, DEX treatment could reverse the inflammatory changes in asthma model mice airway, rescue the cognitive impairment and improve the synaptic plasticity. Besides, DEX significantly decreased the expression of HIF-1α and HIF-2α in mice brain and lung. These processes may be used to decipher the complex interplay and pathological changes between asthma and cognition. This study provides laboratory evidence for the prevention and treatment of cognitive malfunction induced by asthma.